STUDI KOORDINASI SISTEM PERALATAN PROTEKSI PADA PENYULANG PIDADA UNTUK MENDAPATKAN SETTING PENGAMAN YANG SELEKTIF - Adiyaksa Pramana, Kadek; Manuaba, I.B Gede; Maharta Pemayun, A.A Gede (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUM, 2022)
An electric power distribution system must be able to provide electricity to customers. So that the company as a provider is required to provide the best for its customers by increasing the reliability of the distribution system. The more customers who use electricity, the greater the possible fault current, therefore it is necessary to calculate the protection in order to minimize the occurrence of short circuit disturbances. The protection used on the Pidada feeder is Overcurrent Relay (OCR) and Ground Fault Relay (GFR), this protection relay is used to coordinate current settings in accordance with applicable standards and can overcome short-circuit fault currents. In this research, a study of the coordination of the Pidada feeder's OCR and GFR settings was conducted using the DigSILENT PowerFactory 15.1.7 application. Calculations were carried out using the zone division method on the feeder. based on the results of the study, it was found that the Pidada feeder was 0.2 s, the Bulu Indah recloser was 0.1 s and the Padang Udayana recloser was 0.02 s. Then on and the ground fault relay (GFR) obtained results on the Pidada feeder 0.2 s, Bulu Indah recloser 0.1 s and Padang Udayana recloser 0.08 using standard inverse characteristics. The results of this study are in accordance with the applicable standards, where the standard used is IEC 60255 with a drading time of 0.3-0.5 seconds.